Pengaruh Faktor-faktor Motivasi terhadap Kinerja Karyawan pada PT Hadji Kalla Makassar - Musran Munizu (Jurnal Aplikasi Manajemen, 2010)
The purposes of this research are to analyze: (1) how likely the factors of motivation which consists of phyciological needs, safety needs, social needs, esteem needs, and self actualization needs affect to employee performance; and (2) which of those factors would be dominantly affected to employee performance at Hadji Kalla Corporation Makassar. The population in this research includes all employee at Hadji Kalla Corporation. The number of population were 360 persons. There were 90 respondents participated in the survey. The respondents are chosen using simple random sampling from population. The data which using in this research consists of primer data and secondary data that collected by observation, interview, questionnaire, and documentation. Methods of analyses used in this research both descriptive analysis, and multiple regression analysis which performed with SPSS for windows. The results indicated the following: (1) In simultaneous way, the factors of motivation which consists of phyciological needs, safety needs, social needs, esteem needs, and self actualization needs have significantly effect to employee performance; and (2) physiological need is the most dominant variable that affecting the employee performance at Hadji Kalla Corporation Makassar (t-hitung = 3,883; a = 0,000).Keywords: motivation factors, phyciological needs, safety needs, social needs, esteem needs, self actualization needs, employee performance.